Articulating fertilizer subsidy effects on women’s diet quality by food supply source in Mali - Amidou Assima; Giacomo Zanello; Melinda Smale (CABI Agriculture and Bioscience)
Abstract Background Mali’s fertilizer subsidy program aims to reduce food insecurity among the nation’s predominantly rural people by jump-starting productivity gains of major crops. This paper contributes to sparse evidence regarding its effects. Methods Theory predicts that agricultural productivity can affect diet quality directly through two channels. The production channel influences the availability of food for household consumption or sale. The income pathway, resulting from sales, leads to household food expenditure. We test this hypothesis by applying propensity score matching methods to farm household survey data collected from 2400 households in Mali in 2018. Results We find that the overall effect of the fertilizer subsidy on women’s dietary diversity is positive in the Niger Delta and negative on the Koutiala Plateau. Further examination by food supply source reveals no subsidy effects on the dietary diversity provided by on-farm production in either zone. The subsidy negatively influences dietary diversity of foods sourced as gifts in the Niger Delta. Subsidy effects on dietary diversity accessed through food purchases are strong and positive in the Niger Delta, but negative on the Koutiala Plateau. The Koutiala Plateau is found in the region of Sikasso, where rising incomes from cotton production, which is the major export crop of the region and of the nation, have been shown not to alleviate poverty and malnutrition (a dilemma known as the “Sikasso Paradox”). Conclusions Our approach reveals that additional income from increased yields stimulated by subsidized fertilizer can enable off-farm purchases of more nutritious food and thereby improve nutritional outcomes for women.